ANALISIS NILAI SOSIOKULTURAL DALAM NOVEL LAKSAMANA MALAHAYATI SANG PEREMPUAN KEUMALA KARYA ENDANG MOERDOPO - Eli Nurliza; Erfinawati Erfinawati; Cut Nurul Fahmi; Faudi Faudi; Irwan Irwan; Nursafiah Nursafiah (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The purpose of this research is to describe the sociocultural values in the novel Laksamana Malahayati Sang Perempuan Keumala by Endang Moerdopo. The method used in this research is descriptive method. The data source of this research is the novel Laksamana Malahayati Sang Perempuan Keumala by Endang Moerdopo 2018. The data collection method in this research is reading, recording, and categorizing the novel Laksamana Malahayati Sang Perempuan Keumala by Endang Moerdopo. Data analysis techniques in this research are data reduction, data presentation, and conclusion drawing. The sociocultural values contained in this novel, namely the way of thinking, attitudes and beliefs, the way characters believe in something, social values and norms, the way of living traditions/habits that can be seen from the attitude of the character Keumala Hayati in fighting for what she wants